Tracing prehistoric past human routes in the Pyrenees: new data about chert procurement at Montlleó open-air site (Prats i Sansor, Spain) - Marta Sánchez de la Torre; Xavier Mangado; François-Xavier Le Bourdonnec; Bernard Gratuze; Mathieu Langlais; Oriol Mercadal; Josep Maria Fullola (UISPP Journal)
In this work we have analysed the provenance of the lithic raw materials recovered during the excavation campaigns at two Mesolithic sites of the Cantabrian Mountains: La Uña (levels III and IV) and El Espertín (level II). From the data obtained, differences between the two deposits and their levels have been observed, with sourcing of very similar lithic resources, but with important differences in the percentages. In the case of El Espertín there is a greater contribution of varieties from the La Liébana area (NE of Picos de Europa) while at La Uña the NW varieties percentages are higher highlighting in both cases the exclusive origin from the northern slope of the Cantabrian Mountains with the exception of Alba radiolarite, a widely distributed raw material.